Live streaming viewing as functional alternatives to interpersonal interaction: who do you think he/she is? - Long, Quan (Kansas State University, 2019)
Based on the Uses and Gratifications (U&G) approach and Parasocial Interaction (PSI) theory, this study examined how people use live streaming platforms in China. Uniquely, it sought to understand the effect of romantic relationships on how and why people watch Host Live Shows (HLSs) and explored the relationships between Chinese audiences and live- streamers. Through an online survey, four viewing motivations were identified: Community Building, Ego-boost, Escape, and Bandwagon. Ego-boost is a relatively new motivation of media use, which means audiences watch and interact with HLSs to get compliments, self-confidence, self- validation, and ego-boosts. This study found audiences’ perceived realism and PSI were both very neutral. However, emotion projection of audiences onto streamers was observed – most viewers highly agree that streamers are their friends. Moreover, this study found the quality of interpersonal communication is affecting audiences’ HLS dependence and the degree of PSI, while the quantity of interpersonal communication might not be – the more satisfied a person is about his/her interpersonal communication, the heavier he/she depends on HLSs and the stronger his/her PSI is. As expected, the degrees of both romantic relationship status and romantic relationship satisfaction influence people’s HLS use. While compared with females, males are affected by romantic relationships more, both the status and satisfaction level. Lastly, when it comes to people’s romantic lives and social lives, HLSs are more likely to be used as alternatives to meet their unsatisfied needs from their “real partners.”
Keywords: Social live streaming services; Uses and gratifications approach; Parasocial interaction theory; Media as functional alternatives; Media dependency